Antibiotic resistance and virulence characteristics of four carbapenem-resistant Klebsiella pneumoniae strains coharbouring blaKPC and blaNDM based on whole genome sequences from a tertiary general teaching hospital in central China between 2019 and 2021. (February 2023) - Bai, Jing; Liu, Yujie; Kang, Jianbang; Song, Yan; Yin, Donghong; Wang, Shuyun; Guo, Qian; Wang, Jing; Duan, Jinju
Abstract: Objective: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection is a worldwide health issue that poses a serious threat to public health. This study summarizes the clinical features of four patients with CRKP coproducing NDM and KPC infections and further analyses the molecular typing, resistance and virulence factors of the four CRKP strains. Methods: Of the twenty-two CRKP isolates, four strains coharbouring bla KPC and bla NDM isolated from four patients were screened by Sanger sequencing between October 2019 and April 2021. Demographics, clinical and pathological data of the four patients were collected through electronic medical records. Antimicrobial susceptibility testing, biofilm formation assays and serum bactericidal assays were performed on the four isolates. The antibiotic resistance and virulence genes were investigated by whole-genome sequencing. Sequence types (STs) were determined by multilocus sequence typing, and serotypes were identified by wzi gene sequencing. Results: Three patients recovered, and one patient stopped treatment. Four strains were multiple carbapenemase producers: KPC-2, NDM-4, SME-5 and IMI-4 coproducer; KPC-2, NDM-1 and SME-3 coproducer; KPC-2, NDM-1 and IMI-3 coproducer; KPC-2 and NDM-5 coproducer. They also harboured ESBL genes and mutations in the efflux pump regulator genes. They were multidrug resistant but sensitive to tigecycline and colistin. Four isolates had moderate biofilm-forming abilities and carried various virulence genes, including siderophores, type 1 fimbriae and E. coli common pilus. Only the NO. 3 strain was resistant to the serum. The STs and serotypes of the four strains were ST11 and KL64, ST337 and none, ST307 and KL102KL149KL155, and ST29 and K54, respectively. Conclusion: Four CRKP strains coharbouring bla KPC and bla NDM also carried other carbapenemase genes. Notably, the NO. 1 isolate carrying four carbapenemase genes has not been reported globally until now. Four strains exhibited a high level of resistance to multiple antibiotics. Additionally, three of the four patients were exposed to invasive medical devices that provided an environment for biofilm formation. Meanwhile, three strains with adhesion genes as moderate biofilm formers might form biofilms resulting in long hospital stays, increasing therapeutic difficulty, and even treatment failure. This study reminds clinicians that CRKP strains with multiple carbapenemase genes emerged in our hospital, and stronger measures should be taken to the control of nosocomial infections. Highlights: The genetic characterizations of four K . pneumoniae strains coharbouring bla KPC and bla NDM were performed. K. Pneumoniae  with four carbapenemase genes ( bla NDM-4  +  bla KPC-2  +  bla SME-5  +  bla IMI-4 ) was firstly isolated till now. Three strains colonized the surfaces of medical instruments to form biofilms, which increased the difficulty of treatment.